Analisis Kualitas Pelayanan Terhadap Kepuasan Nasabah Tabungan Haji PT Travel Umrah Dan Haji Di Provinsi Lampung - Andriyani, Fitri; Harris, Allan; Reza, Muhammad Faizal (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
The purpose of this study is to evaluate the impact of PT Travel Umrah and Hajj's hajj savings service on customer satisfaction in the province of Lampung. Muslims consider the Hajj and Umrah pilgrimages to be imperative, and travel companies that assist with these pilgrimages provide savings plans to clients who are unable to afford them. The degree to which customer happiness is influenced by the quality of service and Hajj savings products offered to them, therefore discouraging them from moving to other banks, is the research problem in this study. The main goal of this research is customer happiness. Customer satisfaction increases with the caliber of both the Hajj savings product and the service rendered. A quantitative approach is used in this study to gather both primary and secondary data. With a sample size of 100 consumers, the research population comprises 5,010 persons who are Hajj savings clients in 2022. A value of 0.270 from multiple linear regression analysis indicates a strong positive relationship between customer happiness and service quality.